Predictors of rehospitalization due to violent behavior in patients with psychotic disorders with a history of violent behavior - Korkmaz, Ulaş; Şimşek, Meltem Hazel (Frontiers in Psychiatry, 2025)
BackgroundSome individuals with psychotic disorders may exhibit violent behavior, necessitating psychiatric hospitalization to ensure both patient care and public safety. Understanding factors behind post-discharge rehospitalization due to violence is crucial. This study aims to examine the association between treatment adherence, psychiatric follow-up frequency, and prescribed medications with the risk of violent-behavior-related rehospitalization in patients with psychotic disorders.MethodThis retrospective cohort study included 68 patients diagnosed with psychotic disorders under mandatory forensic psychiatric follow-up between January 2022 and February 2025. Patients were categorized into two treatment groups: oral antipsychotic treatment and long-acting injectable (LAI) antipsychotic treatment. The primary outcome was rehospitalization due to violent behavior. Binary logistic regression and Cox regression analyses were performed to identify predictors of rehospitalization and treatment adherence.ResultsThe mean age was 46.76 years. 80.9% of the patients were male, and 70.6% were adherent to treatment. During the follow-up period, 14.7% of the patients were rehospitalized due to violent behavior. Non-adherent patients had a significantly higher risk of rehospitalization (p < 0.001), with a 15-fold increased risk compared to adherent patients. While LAI antipsychotic use, regular follow-up at Community Mental Health Centers, and more frequent psychiatric evaluations were associated with lower rehospitalization rates, these effects did not reach statistical significance.ConclusionsTreatment adherence is a key factor in preventing rehospitalization due to violent behavior. Given its substantial predictive value, interventions targeting adherence, such as LAI antipsychotic use and psychosocial support, should be prioritized. Future studies should include objective medication adherence measures, long-term follow-up, and additional clinical outcomes.